2023
DOI: 10.1037/adb0000838
|View full text |Cite
|
Sign up to set email alerts
|

A randomized pilot trial of a mobile delivered brief motivational interviewing and behavioral economic alcohol intervention for emerging adults.

Abstract: Objective: Mobile health (mHealth) interventions show potential to broaden the reach of efficacious alcohol brief motivational interventions (BMIs). However, efficacy is mixed and may be limited by low participant attention and engagement. The present study examined the feasibility, acceptability, and preliminary efficacy of a live text-message delivered BMI in a pilot randomized clinical trial. Method: Participants were 66 college students (63.6% women; 61.9% White; M age = 19.95, SD = 1.66) reporting an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…How to improve motivation when feedback is delivered through the Web or an app may require additional considerations for better engagement and outcome. Recent studies that provided synchronous teleconferencing (e.g., Zoom) or text‐based intervention have demonstrated the feasibility and preliminary effectiveness (e.g., Gex et al, 2022). With the COVID‐19 pandemic, no‐contact in‐person meetings have proliferated and have been generally accepted (Mark et al, 2022; Oliveira et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…How to improve motivation when feedback is delivered through the Web or an app may require additional considerations for better engagement and outcome. Recent studies that provided synchronous teleconferencing (e.g., Zoom) or text‐based intervention have demonstrated the feasibility and preliminary effectiveness (e.g., Gex et al, 2022). With the COVID‐19 pandemic, no‐contact in‐person meetings have proliferated and have been generally accepted (Mark et al, 2022; Oliveira et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, by collecting information about the degree of problematic substance use, we might be able to discern whether in cases of less severe problematic substance use, EFT could operate as a stand-alone intervention, and in cases of more severity, it could complement evidence-based substance use treatments to heighten their effect. In fact, recent studies have shown the promise of EFT as an adjunct to more comprehensive treatments for individuals who met criteria for alcohol use disorder (Meshesha et al, 2020) and as an independent treatment for individuals who self-reported heavy drinking two times per month (Gex et al, 2022). Similarly, it is possible that EFT may be best utilized as a stand-alone treatment in cases in which the goal is harm reduction versus abstinence by allowing individuals to preexperience the future to avoid negative consequences arising from substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, not only is EFT consistent with the tenets of cognitive behavioral therapy, but it can also be seamlessly integrated into various evidence-based treatment approaches. In fact, two recent studies showed the ease and feasibility of integrating an EFT task into an evidence-based brief motivational interviewing protocol that included discussions of alternative, substance-free activities in a clinical sample with alcohol use disorder (Meshesha et al, 2020) and in a college sample that reported heavy drinking (Gex et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, results highlight the opportunity to significantly reduce risky drinking with long‐term automated messaging interventions that are scalable and low‐effort on participants. Given the opportunity to improve automated interventions with clinician or coach‐supported messaging [68], the studies highlighting the efficacy of human‐supported messaging in alcohol reduction [69] and the rise of conversational artificial intelligence, hybrid models should be explored in future studies. Given both the debilitating personal consequences of excessive alcohol consumption and the economic burden and costs to society [10], reducing binge drinking episodes by 8.2 a month and weekly drinking by 12.9 drinks per week can have a measurable impact on public health through rapid scaling without significant implementation costs.…”
Section: Discussionmentioning
confidence: 99%